2016
DOI: 10.1371/journal.pone.0153496
|View full text |Cite
|
Sign up to set email alerts
|

An Estimate of the Incidence of Prostate Cancer in Africa: A Systematic Review and Meta-Analysis

Abstract: BackgroundProstate cancer (PCa) is rated the second most common cancer and sixth leading cause of cancer deaths among men globally. Reports show that African men suffer disproportionately from PCa compared to men from other parts of the world. It is still quite difficult to accurately describe the burden of PCa in Africa due to poor cancer registration systems. We systematically reviewed the literature on prostate cancer in Africa and provided a continent-wide incidence rate of PCa based on available data in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
119
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(133 citation statements)
references
References 83 publications
5
119
0
Order By: Relevance
“…[1][2][3] A systematic review of estimates of the incidence of cancer among men in Africa reported median prostate cancer incidence rates ranging from 19.5 to 39.0 per 100,000 population. 4 In Nigeria, similar to the situation in other countries in sub-Saharan Africa, prostate cancer is the most common cancer in men, with evidence of increasing morbidity and mortality from the disease. 5,6 Studies conducted in North-Western Nigeria also reported high burden of prostate cancer.…”
Section: Introductionmentioning
confidence: 89%
“…[1][2][3] A systematic review of estimates of the incidence of cancer among men in Africa reported median prostate cancer incidence rates ranging from 19.5 to 39.0 per 100,000 population. 4 In Nigeria, similar to the situation in other countries in sub-Saharan Africa, prostate cancer is the most common cancer in men, with evidence of increasing morbidity and mortality from the disease. 5,6 Studies conducted in North-Western Nigeria also reported high burden of prostate cancer.…”
Section: Introductionmentioning
confidence: 89%
“…Along with an increase in mortality rates, African-American men are generally younger at diagnosis, present with higher tumor grade and volume at surgery, and are at a greater potential for metastasis (4). Within Africa, a greater disease burden has been suggested (1,6). The Southern African Prostate Cancer Study (SAPCS) has shown that South African men present with a 2-fold increase in aggressive disease compared with age-adjusted African Americans (7).…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, a recent systematic and meta-analytical review reported a continent-wide pooled incidence rate of 22.0 (95% CI: 19.93-23.97) per 100 000 population [5]. The average risk that a man in sub-Saharan Africa (SSA) will develop prostate cancer before the age of 75 years is 3.4% [6].…”
Section: Introductionmentioning
confidence: 99%